2015
DOI: 10.3390/ijms160510507
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroaustrasulfone Alcohol (WA-25) Impedes Macrophage Foam Cell Formation by Regulating the Transforming Growth Factor-β1 Pathway

Abstract: Atherosclerosis is considered an inflammatory disease. However, clinically used anti-atherosclerotic drugs, such as simvastatin, have many side effects. Recently, several unique marine compounds have been isolated that possess a variety of bioactivities. In a previous study, we found a synthetic precursor of the marine compound (austrasulfone), which is dihydroaustrasulfone alcohol (WA-25), has anti-atherosclerotic effects in vivo. However, the detailed mechanisms remain unclear. Therefore, to clarify the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Our previous studies reported that WA-25 impedes the formation of foam cells, which would cause atherosclerosis by activating the transforming growth factor β1 (TGF-β1) pathway. 24 Interestingly, TGF-β1 inhibits AD in NC/Nga mice. 70 However, we also found that WA-25 inhibits angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies reported that WA-25 impedes the formation of foam cells, which would cause atherosclerosis by activating the transforming growth factor β1 (TGF-β1) pathway. 24 Interestingly, TGF-β1 inhibits AD in NC/Nga mice. 70 However, we also found that WA-25 inhibits angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry was performed using modified methods as previously described. 24 After treatment, RAW 264.7 cells were fixed with 4% paraformaldehyde in PBS buffer for 8 min and washed three times with PBS buffer. The cells were blocked with 4% normal goat serum dissolved in PBS containing 0.01% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…TGF-β1, a growth regulatory factor originating from multiple human epithelia, has various biological effects related to cellular proliferation and differentiation, deposition of extracellular matrix, and human immune responses [ 22 ]. TGF-β1 is a key cytokine that regulates cellular growth and controls the balance of extracellular matrix production and degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Austrasulfone effectively decreases 6-OHDA-induced SH-SY5Y cell death. Furthermore, a previous study found that the intermediate product in the synthesis of austrasulfone, dihydroaustrasulfone alcohol, decreases the expression of proinflammatory cytokines such as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX2), thus alleviating neuropathic pain and multiple sclerosis in rats regulating lipid metabolism in macrophages, and inhibiting restenosis [ 35 , 36 , 37 , 38 ]. The above results suggest that the bioactivity of austrasulfone and its intermediate, dihydroaustrasulfone, could be possibly related to their structures.…”
Section: Introductionmentioning
confidence: 99%